Strategies for Improving Organizational Performance ThroughTransformational Leadership - Putri Amalia (Public Studies and Business Administration Journal (PUSBA), 2024)
This study discusses strategies for improving organizational performance throughtransformational leadership. Transformational leadership has been recognized as apowerful approach to driving organizational performance by inspiring and empoweringemployees, as well as fostering a culture of innovation and creativity. In this research,we conducted a systematic literature review to explore the impact of transformationalleadership on organizational performance and formulate effective strategies for itsimplementation. The findings of the research indicate that transformational leadershiphas a positive impact on employee motivation, organizational culture, employeesatisfaction, and innovation levels. Additionally, we identified several key strategies forimplementing transformational leadership, including communicating a compellingvision, empowering and delegating authority, providing mentorship and coaching,encouraging risk-taking and experimentation, building strong relationships and trust,and leading by exampl